Risk factors for unintentional injuries due to falls in children aged 0–6 years: a systematic review. Issue 6 (14th December 2006) - Khambalia, A; Joshi, P; Brussoni, M; Raina, P; Morrongiello, B; Macarthur, C
Abstract : Objective: To identify risk factors for unintentional injuries due to falls in children aged 0–6 years. Design: A systematic review of the literature. Methods: Electronic databases from 1966 to March 2005 were comprehensively searched to identify empirical research that evaluated risk factors for unintentional injuries due to falls in children aged 0–6 years and included a comparison group. Results: 14 studies met the inclusion criteria. Studies varied by the type of fall injury that was considered (ie, bunk bed, stairway, playground or infant walker) and with respect to the quality of evidence. In general, major risk factors for the incidence or severity of injuries due to falls in children included age of the child, sex, height of the fall, type of surface, mechanism (dropped, stairway or using a walker), setting (day care v home care) and socioeconomic status. Conclusion: Despite a high burden, few controlled studies have examined the risk and protective factors for injuries due to falls in children aged 0–6 years. The only study to examine falls from a population health perspective suggests that age, sex and poverty are independent risk factors for injuries due to falls in children.